Anxiety Is Associated With DPPIV Alterations in Children With Selective Mutism and Social Anxiety Disorder: A Pilot Study - Golub, Yulia; Stonawski, Valeska; Plank, Anne-Christine; Eichler, Anna; Kratz, Oliver; Waltes, Regina; von Hörsten, Stephan; Roessner, Veit; Freitag, Christine M. (Frontiers in Psychiatry, 2021)
Background: Both selective mutism (SM) and social anxiety disorder (SAD) are severe pediatric anxiety disorders with the common trait of behavioral inhibition (BI). The underlying pathophysiology of these disorders remains poorly understood, however converging evidence suggests that alterations in several peripheral molecular pathways might be involved. In a pilot study, we investigated alterations in plasma molecular markers (dipeptidyl peptidase-4 [DPPIV], interleukin-6 [IL-6], tumor necrosis factor-beta [TNF-beta] and neuropeptide-Y [NPY]) in children with SM, SAD, and healthy controls, as well as the correlation of these markers to symptom severity.
CRIS-Team WoS Importer:2021-07-23